2017
DOI: 10.1123/jab.2017-0058
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and Validity of an Acromion Marker Cluster for Recording Scapula Posture at End Range Clavicle Protraction, Retraction, Elevation, and Depression

Abstract: Acromion marker cluster (AMC) methods have been shown to accurately track scapula motion during humeral elevation below 90°, however, their accuracy has not been assessed in shoulder girdle motion such as clavicle protraction, retraction, elevation, and depression independent of humeral movement. The aim of this study was to examine the reliability and validity of the AMC method to record scapula orientation at end range clavicle protraction, retraction, elevation, and depression. The right scapulae of 22 fema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…None of these validated the skin marker model against markers on intracortical pins, however. More recently, a setup similar to the present study compared an AMC model to a scapula locator at end range elevation, depression, protraction and retraction of the clavicle without elevating the arm, reporting mean RMSEs for the scapular rotations of less than 10° [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…None of these validated the skin marker model against markers on intracortical pins, however. More recently, a setup similar to the present study compared an AMC model to a scapula locator at end range elevation, depression, protraction and retraction of the clavicle without elevating the arm, reporting mean RMSEs for the scapular rotations of less than 10° [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Both scapulae utilized a three non-collinear acromion marker cluster (AMC) placed on the spine of the scapula as it transitioned into the acromion. Bet-Or et al ( 2017 ) found the AMC method to track scapula kinematics during shoulder elevation has high test–retest reliability (intraclass correlation coefficient = 0.90–0.98) and error of (SEM = max 2.3 deg, MDC = max 6.2 deg) for all 3 scapular rotations. Additional markers were placed on the 7th cervical vertebrae spinous process, 8th thoracic vertebrae spinous process, jugular notch, xiphoid process, a four-marker cluster on each arm midway between the lateral epicondyle and the lateral aspect of the acromion.…”
Section: Methodsmentioning
confidence: 99%
“…We estimated the glenohumeral joint location using a functional approach [ 16 , 17 ]. To this end, a temporary cluster was attached to the skin covering the acromion to track the scapula to allow for measurement of relative motion between the upper arm and scapula [ 18 ]. The scapular cluster was placed at the junction of the scapular spine and acromion [ 19 ].…”
Section: Methodsmentioning
confidence: 99%